Saling ketergantungan positif dari nilai kerja sama dalam model pembelajaran kooperatif tipe teams games tournament (tgt) pada pembelajaran matematika kelas III sekolah dasar - Nur Naim Muaziz; Joko Daryanto; Sandra Bayu Kurniawan (Didaktika Dwija Indria, 2024)
The purpose of this study was to show the value of student cooperation through the Teams Games Tournament (TGT) learning model in mathematics learning for grade III of elementary school. This study uses a descriptive qualitative research method. The data used are the results of observations in mathematics learning on the material of calculating the circumference of flat shapes and the results of interviews with teachers and grade III students. The data obtained were then analyzed referring to the Miles & Huberman analysis model. The results of this study are through the application of the Teams Games Tournament (TGT) cooperative learning model, students can show the values of cooperation in the form of students depending on each other in positive ways towards their group, including: 1) Students remind group members if they have not done their assignments. 2) Students are willing to help group members if they have difficulties. 3) Students share information needed by the group. The value of cooperation can emerge because implementation of TGT model, students must work in groups. So this model is the right learning model to develop students' cooperation values.